Pendidikan etika bertamu dan menyambut tamu di kisah Nabi Ibrahim dalam Tafsir Nusantara - Hibatullah, Alif (LPPM Universitas Ibn Khaldun, Bogor, 2024)
Moral degradation in guest and host etiquette has become a serious issue, with many people needing more proper conduct in social interactions, leading to various conflicts. Common problems include guests entering homes without permission and hosts providing inadequate receptions. This study aims to analyze the interpretations of Indonesian scholars (mufasir Nusantara) regarding the story of Prophet Ibrahim welcoming his guests, using Roland Barthes' semiotic analysis in a qualitative research framework. The findings highlight that essential guest etiquette includes being polite, greeting before entering, and not inconveniencing the host. For hosts, the critical etiquette is to be friendly and kind, offer a warm welcome with refreshments and engage the guests in conversation to understand their purpose. To instill these ethical values, they can be integrated into the school environment through educational materials derived from the story of Prophet Ibrahim and modeled by teachers greeting students before entering the classroom. Additionally, habituation in the family setting, where parents teach children to be polite and welcoming, ensures these values are ingrained from an early age. Abstrak Degradasi moral dalam tata krama tamu dan tuan rumah telah menjadi permasalahan yang serius, karena banyak orang yang memerlukan perilaku yang lebih baik dalam berinteraksi sosial, sehingga menimbulkan berbagai konflik. Masalah yang umum terjadi adalah tamu memasuki rumah tanpa izin dan tuan rumah memberikan sambutan yang tidak memadai. Penelitian ini bertujuan untuk menganalisis penafsiran para ulama Indonesia (mufasir Nusantara) terhadap kisah Nabi Ibrahim menyambut tamunya, dengan menggunakan analisis semiotika Roland Barthes dalam kerangka penelitian kualitatif. Temuan ini menyoroti bahwa etika tamu yang penting mencakup bersikap sopan, memberi salam sebelum masuk, dan tidak merepotkan tuan rumah. Bagi tuan rumah, etiket penting adalah bersikap ramah dan baik hati, memberikan sambutan hangat dengan minuman segar, dan mengajak para tamu berbincang untuk memahami tujuan mereka. Untuk menanamkan nilai-nilai etika tersebut dapat diintegrasikan ke dalam lingkungan sekolah melalui materi pendidikan yang bersumber dari kisah Nabi Ibrahim dan dicontohkan dengan cara guru menyapa siswa sebelum memasuki kelas. Selain itu, pembiasaan dalam lingkungan keluarga, dimana orang tua mendidik anak untuk bersikap sopan dan ramah, memastikan nilai-nilai ini tertanam sejak dini.